What's Wrong with International Financial Markets? - Ricardo Hausmann; Eduardo Fernández-Arias (Inter-American Development Bank, Research Department, 2000)
Recent financial crises and contagion call into question the wisdom of capital account liberalization. There is consensus that something is terribly wrong in the way international financial markets work for developing countries and that fixing is urgent. But what is wrong? Most views in developed countries identify the problems with too much capital flows, attracted by moral hazard. However, our analysis shows that the role of this distortion is being grossly exaggerated and that, in contrast, the main distortions in international financial markets are associated with capital flows being too little, restricted by sovereign risk, and too volatile because of market failures.
Keywords: 330; Internationaler Finanzmarkt; Schwellenländer; Welt